Having faith in the university? Aspects of the relationship between religion and the university - Christo Lombaard (Acta Theologica)
In this paper, five aspects related to the study of religion in the university setting, in its classically liberal mode, are considered. First, the author’s commitment to this kind of university is developed further by noting a surprising new development in academic freedom. Then, the author argues against the a-religious impulses of modernity and discusses the place of the study of religion at the university from three perspectives: the paradigmatic philosophy of science, the sociological continuation of faith and the evolutionary importance of religion. Last, the kinds of relevance that have been, ought to be and are likely to be demanded of theology at the university are discussed briefly.